Matrix-assisted laser desorption ionization-time of flight mass spectrometry meropenem hydrolysis assay with NH4HCO3, a reliable tool for direct detection of carbapenemase activity - Papagiannitsis, Costas C; Študentová, Vendula; Izdebski, Radoslaw; Oikonomou, Olga; Pfeifer, Yvonne; Petinaki, Efthimia; Hrabák, Jaroslav (Journal of clinical microbiology, 2015)
A comparison of a matrix-assisted laser desorption ionization-time of flight mass spectrometric (MALDI-TOF MS) meropenem hydrolysis assay with the Carba NP test showed that both methods exhibited low sensitivity (approximately 76%), mainly due to the false-negative results obtained with OXA-48-type producers. The addition of NH4HCO3 to the reaction buffer for the MALDI-TOF MS assay dramatically improved its sensitivity (98%). Automatic interpretation of the MALDI-TOF MS assay, using the MBT STAR-BL software, generally agreed with the results obtained after manual analysis. For the Carba NP test, spectrophotometric analysis found six additional carbapenemase producers.
Keywords: laboratorní automatizace; hydrolýza; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; beta-laktamasy; bakteriální proteiny; Bacterial Proteins; software; lidé; Sensitivity and Specificity; Buffers; senzitivita a specificita; Electronic Data Processing; automatizované zpracování dat; beta-Lactamases; Thienamycins; Bicarbonates; thienamyciny; Hydrolysis; Software; Automation, Laboratory; spektrometrie hmotnostní - ionizace laserem za účasti matrice; pufry; hydrogenuhličitany; Humans